The Role of Electronic Governance in Achieving Entrepreneurial Orientation Using (GIS): An Empirical Study in the Babylon Water Department - Hsoonee Majroud, Hakim; Abdul Ameer Shamkhi AL Shlah, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims to diagnose the pioneering direction of the Babylon Water Department through its dimensions of (creative, proactive and proactive, strategic vision, investment of opportunities, risk), presenting some suggestions that help the researched organization to take advantage of these dimensions, in addition to learning about the reality of the use of geographic information systems (GIS) in the researched organization and determining the relationship between electronic governance and the orientation of GIS mediation, for the purpose of identifying that relationship, a scale was designed consisting of (77) items distributed on three axes, 220 questionnaires were distributed, 200 of which were valid for statistical analysis were retrieved, that is, with a retrieval rate of (91%), the descriptive analytical method was used to analyze the questionnaire data, statistical tools were used, such as (arithmetic mean, standard deviation, confirmatory factor analysis), the researchers have aimed to test a number of main subsidiary hypotheses related to the relationships of influence and influence between the research variables, also, the moral differences between these variables for the purpose of answering the questions related to the research problem to reach the set goals, the study has reached a number of conclusions, the most important of which is that the Babylon Water Department is working to develop its work and strengthen it towards electronic work to achieve the required pioneering direction despite receiving most of the official orders and books in a traditional paper form, the study has come out set of recommendations, the most important of which is the management of the Babylon Water Department to directly supervise the website of the department as it is an effective means of communication between the citizen and the department through which he can transfer his complaint or shorten the work cadres while performing the tasks assigned to them.